Webservices Theory and Practice - Mohanty, Hrushikesha; Pattnaik, Prasant Kumar; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
This book focuses on web service specification, search, composition, validation, resiliency, security and engineering, and discusses various service specification standards like WSDL, SAWSDL, WSMO and OWLS. The theory and associated algorithms for service specification verification are detailed using formal models like Petrinet, FSM and UML. The book also explores various approaches proposed for web service search and composition, highlighting input/output, parameter-based search, and selection of services based on both functional and non-functional parameters. In turn, it examines various types of composite web services and presents an overview of popular fault handling strategies for each of these types. Lastly, it discusses the standards used for implementing web service security on the basis of a case study, and introduces the Web Service Development Life Cycle (WSDLC), which defines co-operation between several industry partners to develop web services in a more structured way. .
Service Modelling and Verification: A Formal Approach -- Webservice Specification and Discovery -- Non-functional Properties of a Webservice -- Service Composition -- Handling Faults in Composite Webservices -- Webservice Security -- Webservice Development Life Cycle.
Keywords: Telecommunication; Application software; Internet programming; Communications Engineering, Networks; Computer and Information Systems Applications; Web Development